THE EFFECT OF THE TEAMS GAME TOURNAMENT LEARNING MODEL ON CRITICAL THINKING ABILITIES AND MOTIVATION TO LEARN IPAS IN 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Endang Yuliani; Firmansyah (Universitas Majalengka, 2026)
This study aims to determine the effect of the TGT (Teams Games Tournament) Cooperative Learning model on critical thinking skills and student learning motivation in the fifth grade science subject at Tambongwetan 1 Elementary School, Klaten Regency. This type of research is a quasi-experimental study using a Pretest-Posttest Control Group Design. The experimental class was given TGT learning and the control class was given conventional learning. The sampling technique used simple random sampling. The data analysis technique used inferential statistics. The results showed that the average critical thinking skills of the experimental class increased significantly by 30 points, and the control class only increased by 20.8 points. Student learning motivation in the experimental class also experienced a greater increase, namely by 19 points, compared to the control class which only increased by 5.11 points. The results of the inferential analysis showed a significant effect (p <0.001) of the TGT model on both dependent variables. In conclusion, the TGT model is effective for improving students' critical thinking skills and learning motivation in science learning.